2008
DOI: 10.1107/s1600536808033898
|View full text |Cite
|
Sign up to set email alerts
|

4-Iodobenzohydrazide

Abstract: In the structure of the title compound, C7H7IN2O, the hydrazide group is inclined at 13.3 (3)° with respect to the benzene ring. The structure is stabilized by inter­molecular N—H⋯N and N—H⋯O hydrogen bonds involving the hydrazide group, resulting in six- and ten-membered rings with R 2 2(6) and R 2 2(10) graph-set notations, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In order to study the biological behaviour of 4-methoxybenzhydrazide and to investigate the change in activity due to complexation with vanadium center, we have synthesized (I) and report its crystal structure in this paper. The structures of benzhydrazide (Kallel et al, 1992), para-chloro (Saraogi et al, 2002), para-bromo (Ashiq, Jamal et al, 2008) and para-iodo (Jamal et al, 2008) analogues of (I) have already been reported.…”
Section: Data Collectionmentioning
confidence: 99%
“…In order to study the biological behaviour of 4-methoxybenzhydrazide and to investigate the change in activity due to complexation with vanadium center, we have synthesized (I) and report its crystal structure in this paper. The structures of benzhydrazide (Kallel et al, 1992), para-chloro (Saraogi et al, 2002), para-bromo (Ashiq, Jamal et al, 2008) and para-iodo (Jamal et al, 2008) analogues of (I) have already been reported.…”
Section: Data Collectionmentioning
confidence: 99%
“…For the biological activity of hydrazides, see: Ashiq, Ara et al (2008); Ara et al (2007); Maqsood et al (2006); For related structures, see: Ashiq, Jamal et al (2008); Jamal et al (2008Jamal et al ( , 2009; Kallel et al (1992); Ratajczak et al (2001); Saraogi et al (2002). For graph-set notation of hydrogen-bond motifs, see: (Bernstein et al 1995).…”
Section: Related Literaturementioning
confidence: 99%
“…The title compound was found to be antifungal (Maqsood et al, 2006). The structures of benzhydrazide (Kallel et al, 1992), and its p-chloro (Saraogi et al, 2002), m-methoxy (Jamal et al, 2009), m-nitro (Ratajczak et al 2001), p-bromo (Ashiq, Jamal et al, 2008) and p-iodo (Jamal et al, 2008) analogues have been reported.…”
Section: Related Literaturementioning
confidence: 99%